2001
DOI: 10.1097/00000539-200104000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Stimuli and Anxiety in Children Undergoing Surgery: A Randomized, Controlled Trial

Abstract: Children are less anxious and show increased compliance during induction when exposed to a single care-provider in a dimmed, quiet operating room with background music.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
46
0
5

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(57 citation statements)
references
References 19 publications
5
46
0
5
Order By: Relevance
“…A wide variety of approaches have been proposed to minimize the potential negative effects of surgery and hospitalization, in particular the use of toys and other entertainment materials [12,[79][80][81], including music [82,83], humor [84], magic [85], hospital clowns [20,86], guided visits to the hospital and operating room [87] and educational preoperative programs [11,66,73,88]. The literature also recommends that preoperative instruments should be brief, portable, inexpensive, and easy to administer [89].…”
Section: Discussionmentioning
confidence: 99%
“…A wide variety of approaches have been proposed to minimize the potential negative effects of surgery and hospitalization, in particular the use of toys and other entertainment materials [12,[79][80][81], including music [82,83], humor [84], magic [85], hospital clowns [20,86], guided visits to the hospital and operating room [87] and educational preoperative programs [11,66,73,88]. The literature also recommends that preoperative instruments should be brief, portable, inexpensive, and easy to administer [89].…”
Section: Discussionmentioning
confidence: 99%
“…Some strategies for managing preoperative anxiety are pharmacologic (eg, sedative premedication) 20,21 ; nonpharmacologic (eg, preoperative visit to the OR) 6 ; the presence of 1 of the 2 parents during the induction of anesthesia 19 ; psychological preparation of the child 22,23 ; and the use of music as a distraction. 24,25 There have not been previous studies that evaluated the efficacy of clowns with respect to preoperative anxiety of children and their parents during the induction of anesthesia. In this study we found that the presence of clowns during the induction of anesthesia was an effective intervention for managing a child's anxiety during the preoperative period.…”
Section: Discussionmentioning
confidence: 99%
“…In another trial, according to Berghmans of 120 children, co-operation at induction did not differ significantly when a video of a fairytale was played before induction [7]. Children exposed to low sensory stimulation were significantly less anxious than control children upon introduction of the anesthesia mask, and more likely to be co-operative during induction, in one trial of 70 children [8]. Music therapy did not show a significant effect on children's anxiety in another trial of 51 children [9].…”
Section: Video Assisted Induction Group In Each Groupmentioning
confidence: 93%